Vanadium oxide and battery using same

By adjusting the content and structure of Li and O, using vanadium oxides with the composition of Li3+x+αV1-xMxO4+α/2, the shortcomings in charge and discharge characteristics and capacity of existing vanadium oxide battery materials have been solved, and significantly improved the Battery performance.

CN119301071APending Publication Date: 2025-01-10PANASONIC INTELLECTUAL PROPERTY MANAGEMENT CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380044363.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-06-06
Filing Date
2023-04-06
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

The existing vanadium oxide battery materials have shortcomings in charge and discharge characteristics and capacity, especially the Li and O content of Li3VO4 and (Li[3-ax+(5-b)y]Ax)(V1-yBy)O4 materials. Inadequate affects the performance of the battery.

Method used

Vanadium oxide with the composition formula Li3+x+αV1-xMxO4+α/2, where 0.03<α<1.0, 0≤x<1.0, M is a 4-valent metal element, such as Ti, by adjusting the content of Li and O and Structure to improve the charging and discharging characteristics and capacity of the battery.

Benefits of technology

The charging and discharging characteristics and capacity of the battery are significantly improved, especially by optimizing the Li and O content, making Li easier to insert and detach from vanadium oxides, enhancing the performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119301071A_ABST
    Figure CN119301071A_ABST
Patent Text Reader

Abstract

This vanadium oxide is represented by compositional formula (1): Li < 3 + x + alpha > V < 1-x > M < x > O < 4 + alpha > / 2. Here, in the compositional formula (1), 0.03 lt is satisfied; [alpha] [lt]; 1.0 and 0 < = xlt; and M is at least one selected from the group consisting of tetravalent metal elements. A battery (1000) according to the present disclosure is provided with a positive electrode (201), a negative electrode (203), and an electrolyte layer (202) disposed between the positive electrode (201) and the negative electrode (203). A negative electrode (203) includes the vanadium oxide of the present disclosure.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to vanadium oxides and batteries using the same. Background Art

[0002] Patent Document 1 discloses a non-aqueous secondary battery using Li 3 VO 4 as negative electrode active material.

[0003] Patent Document 2 discloses a co-fired all-solid-state battery using (Li [3-ax+(5-b)y] A x )(V 1-y B y ) 4 The negative electrode active material shown. Here, A is at least one element selected from the group consisting of Mg, Al, Ga and Zn, and B is at least one element selected from the group consisting of Zn, Al, Ga, Si, Ge, P and Ti. x and y satisfy 0≤x≤1.0 and 0≤y≤0.6, respectively. a is the average valence of A, and b is the average valence of B.

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: Japanese Patent Application Publication No. 2008-77847

[0007] Patent Document 2: International Publication No. 2019 / 044902 Summary of the invention

[0008] Problems to be solved by the invention

[0009] The present disclosure provides novel vanadium oxides that can be used as battery materials.

[0010] Means used to solve problems

[0011] The vanadium oxide disclosed in the present invention has a composition formula (1): Li 3+x+α V 1-x M x O 4+α / 2 express,

[0012] Here, in the aforementioned composition formula (1),

[0013] satisfies 0.03<α<1.0 and 0≤x<1.0, and

[0014] M is at least one selected from the group consisting of tetravalent metal elements.

[0015] Effects of the Invention

[0016] The present disclosure provides novel vanadium oxides that can be used as battery materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 A cross-sectional view of a battery 1000 according to a second embodiment is shown.

[0018] Figure 2 A cross-sectional view of an electrode material 1100 according to the second embodiment is shown.

[0019] Figure 3 This is a graph showing the initial discharge characteristics of the battery of Example 1. DETAILED DESCRIPTION

[0020] (Overview of one aspect of the present disclosure)

[0021] The vanadium oxide of the first embodiment of the present disclosure has a composition formula (1): Li 3+x+α V 1-x M x O 4+α / 2 express,

[0022] Here, in the aforementioned composition formula (1),

[0023] satisfies 0.03<α<1.0 and 0≤x<1.0, and

[0024] M is at least one selected from the group consisting of tetravalent metal elements.

[0025] The vanadium oxide of the first embodiment is a novel substance that can be used as a battery material. The vanadium oxide of the first embodiment can be used, for example, as a negative electrode active material. The vanadium oxide of the first embodiment is suitable for improving, for example, the charge and discharge characteristics of a battery, and is suitable for improving, for example, the battery capacity.

[0026] In the second embodiment of the present disclosure, for example, the vanadium oxide according to the first embodiment may satisfy 0 in the composition formula (1). <x<1.0。

[0027] The vanadium oxide of the second solution is more suitable for increasing the battery capacity.

[0028] In the third embodiment of the present disclosure, for example, the vanadium oxide according to the second embodiment may satisfy 0 in the composition formula (1). <x≤0.1。

[0029] The vanadium oxide of the third option is more suitable for increasing the battery capacity.

[0030] In a fourth aspect of the present disclosure, for example, in the vanadium oxide according to any one of the first to third aspects, in the composition formula (1), M may contain Ti.

[0031] The vanadium oxide of the fourth scheme is more suitable for improving the battery capacity.

[0032] In a fifth aspect of the present disclosure, for example, the vanadium oxide according to any one of the first to fourth aspects may satisfy 0.04≤α≤0.95 in the composition formula (1).

[0033] The vanadium oxide of the fifth scheme is more suitable for improving the battery capacity.

[0034] In a sixth aspect of the present disclosure, for example, the vanadium oxide according to the fifth aspect may satisfy 0.06≤α≤0.93 in the composition formula (1).

[0035] The vanadium oxide of the sixth scheme is more suitable for improving the battery capacity.

[0036] In the seventh aspect of the present disclosure, for example, the vanadium oxide according to the sixth aspect may satisfy 0.1≤α≤0.6 in the composition formula (1).

[0037] The vanadium oxide of Scheme 7 is more suitable for improving battery capacity.

[0038] In the eighth aspect of the present disclosure, for example, the vanadium oxide according to the seventh aspect may satisfy 0.14≤α≤0.57 in the composition formula (1).

[0039] The vanadium oxide of Scheme 8 is more suitable for improving battery capacity.

[0040] A battery according to a ninth aspect of the present disclosure includes:

[0041] positive electrode,

[0042] Negative electrode, and

[0043] an electrolyte layer disposed between the positive electrode and the negative electrode,

[0044] The negative electrode includes the vanadium oxide according to any one of the first to eighth aspects.

[0045] The battery of the ninth aspect has excellent charge and discharge characteristics.

[0046] In a tenth aspect of the present disclosure, for example, in the battery according to the ninth aspect, the negative electrode may further include a conductive auxiliary agent.

[0047] The battery of the tenth aspect can improve the electron conductivity of the negative electrode. Therefore, the battery of the tenth aspect has more excellent charge and discharge characteristics.

[0048] Hereinafter, embodiments of the present disclosure will be described with reference to the drawings. The present disclosure is not limited to the following embodiments.

[0049] (First embodiment)

[0050] The vanadium oxide of the first embodiment is composed of

[0051] Composition formula (1): Li 3+x+α V 1-x M x O 4+α / 2

[0052] Here, in the composition formula (1), 0.03<α<1.0 and 0≤x<1.0 are satisfied, and M is at least one selected from the group consisting of tetravalent metal elements.

[0053] The vanadium oxide of the first embodiment can be used as a battery material. The vanadium oxide of the first embodiment can be used, for example, as a negative electrode active material. The vanadium oxide of the first embodiment can be used, for example, to obtain a battery with excellent charge and discharge characteristics. The vanadium oxide of the first embodiment is suitable for increasing the battery capacity. An example of a battery is an all-solid-state battery. The all-solid-state battery can be a primary battery or a secondary battery.

[0054] When 0.03<α<1.0 is satisfied in the composition formula (1), the capacity of a battery using the vanadium oxide of the first embodiment is improved, for example. This is because Li can be easily inserted into and extracted from the vanadium oxide of the first embodiment.

[0055] The amount of Li and O represented by α in the composition formula (1) may be enclosed in the particles of the vanadium oxide, or may exist outside the particles as a second phase different from the first phase constituting the particles. It should be noted that the vanadium oxides disclosed in Patent Documents 1 and 2 do not contain Li and O in an amount equivalent to that represented by α.

[0056] In the composition formula (1), 0.04≤α≤0.95 may be satisfied. According to this structure, the vanadium oxide of the first embodiment can improve the battery capacity.

[0057] In the composition formula (1), 0.06≤α≤0.93 may be satisfied. According to this structure, the vanadium oxide of the first embodiment can improve the battery capacity.

[0058] In the composition formula (1), 0.1≤α≤0.6 may be satisfied. According to this structure, the vanadium oxide of the first embodiment can further improve the battery capacity.

[0059] In the composition formula (1), 0.14≤α≤0.57 may be satisfied. According to this structure, the vanadium oxide of the first embodiment can further improve the battery capacity.

[0060] The upper limit value and the lower limit value of the range of α in the compositional formula (1) can be defined by any combination selected from values greater than 0.03 (i.e., 0.03 < α), 0.04, 0.06, 0.1, 0.14, 0.24, 0.25, 0.32, 0.57, 0.6, 0.93, 0.95 and less than 1.0 (i.e., α < 1.0).

[0061] In the compositional formula (1), 0 < x < 1.0 can be satisfied. According to this configuration, the vanadium oxide of the first embodiment can increase the battery capacity.

[0062] In the compositional formula (1), 0 < x ≤ 0.1 can be satisfied. According to this configuration, the vanadium oxide of the first embodiment can further increase the battery capacity.

[0063] The upper limit value and the lower limit value of the range of x in the compositional formula (1) can be defined by any combination selected from values greater than 0 (i.e., 0 < x), 0.05, 0.1 and less than 1.0 (i.e., x < 1.0).

[0064] In the compositional formula (1), when x satisfies the above range, Li becomes more likely to be inserted / extracted into / from the vanadium oxide of the first embodiment. Therefore, as described above, the vanadium oxide of the first embodiment can increase the battery capacity.

[0065] As described above, M is at least one selected from tetravalent metal elements. Examples of tetravalent metal elements include: Ti, Zr, Si, Ge or Sn.

[0066] In the compositional formula (1), M may contain Ti. According to this configuration, the vanadium oxide of the first embodiment can increase the battery capacity. M can be Ti.

[0067] The shape of the vanadium oxide of the first embodiment is not limited. Examples of this shape include: needle-like, spherical and ellipsoidal. The vanadium oxide of the first embodiment can be granular. The vanadium oxide of the first embodiment can be formed in the shape of pellets or plates.

[0068] When the vanadium oxide of the first embodiment is granular (e.g., spherical), the particles of the vanadium oxide may have a median particle diameter of 0.1 μm or more and 100 μm or less, or may have a median particle diameter of 0.5 μm or more and 10 μm or less. Thus, the vanadium oxide of the first embodiment and other materials can be well dispersed. Other materials refer to, for example, solid electrolytes.

[0069] The median particle diameter of the particles refers to the particle diameter (d50) corresponding to 50% of the volume cumulative in the volume-based particle size distribution. The volume-based particle size distribution can be measured by a laser diffraction measuring device or an image analysis device.

[0070] <Method for producing vanadium oxide>

[0071] The vanadium oxide according to the first embodiment can be produced by the following method.

[0072] A raw material powder is prepared so as to have a target composition. Examples of the raw material powder include oxides, hydroxides, carbonates, nitrates, or organic salts.

[0073] As an example, assuming that in the composition formula (1): Li 3+x+α V 1-x M x O 4+α / 2 In the vanadium oxide shown, M is Ti and x is 0.05 when the raw materials are mixed. First, prepare the raw material powder with α being 0. 2 CO 3 、V 2 O 5 and TiO 2 Press Li 2 CO 3 :V 2 O 5 :TiO 2 =(3.05 / 2):(0.95 / 2):0.05 molar ratio. To the raw material powder prepared at such a molar ratio, a substance as a Li source, such as Li 2 CO 3 , the raw material powders are mixed. The amount of the excess portion of the excessively mixed Li source can be appropriately determined, for example, according to the value of α in the target composition and the substance used as the Li source. As an example, in order to produce a vanadium oxide satisfying 0.03<α<1.0, the Li source can be used in excess in the range of 0.5 mass % to 40 mass %, or in the range of 1 mass % to 30 mass %, relative to the amount of the Li source whose molar ratio is determined with α being 0.

[0074] Can replace Li 2 CO 3 Lithium hydroxide or its hydrate is used.

[0075] The reaction product can be obtained by calcining the mixture of raw material powders. The atmosphere during calcination can be air or an inert gas atmosphere. The inert atmosphere is, for example, an argon atmosphere or a nitrogen atmosphere.

[0076] Alternatively, the mixture of raw material powders may be reacted chemically and mechanically (by chemical mechanical milling) in a mixing device such as a planetary ball mill to obtain a reaction product.

[0077] By these methods, the vanadium oxide of the first embodiment can be obtained.

[0078] Here, the molar ratio of the raw materials when mixed is not necessarily the same as the molar ratio of the reactants because the raw materials may be incorporated into the reactants by evaporation or the like during the reaction.

[0079] The composition of the vanadium oxide, for example, the value of x and the value of α in the composition formula (1) can be determined, for example, by high-frequency inductively coupled plasma (ICP) emission spectroscopy, atomic absorption spectrometry, or EPMA (Electron Probe Micro Analyzer, electron probe microanalysis) method. The value of x in the composition formula (1) can be obtained based on the amount of element M in the vanadium oxide. The value of α in the composition formula (1) can be obtained based on the amount of Li and the amount of element M in the vanadium oxide.

[0080] (Second embodiment)

[0081] The second embodiment will be described below, while matters already described in the first embodiment will be omitted as appropriate.

[0082] The battery of the second embodiment includes a positive electrode, an electrolyte layer, and a negative electrode. The electrolyte layer is disposed between the positive electrode and the negative electrode. The negative electrode includes the vanadium oxide of the first embodiment.

[0083] The battery of the second embodiment has excellent charge and discharge characteristics.

[0084] Figure 1 A cross-sectional view of a battery 1000 according to a second embodiment is shown.

[0085] The battery 1000 includes a positive electrode 201 , an electrolyte layer 202 , and a negative electrode 203 . The electrolyte layer 202 is disposed between the positive electrode 201 and the negative electrode 203 .

[0086] The positive electrode 201 contains positive electrode active material particles 204 and solid electrolyte particles 100 .

[0087] The electrolyte layer 202 contains an electrolyte material. The electrolyte material is, for example, a solid electrolyte material.

[0088] The negative electrode 203 contains negative electrode active material particles 205 and solid electrolyte particles 100 .

[0089] The negative electrode active material particles 205 are particles containing the vanadium oxide of the first embodiment. The negative electrode active material particles 205 may be particles containing the vanadium oxide of the first embodiment as a main component. The particles containing the vanadium oxide of the first embodiment as a main component refer to particles containing the vanadium oxide of the first embodiment as the largest component in terms of mass ratio. The negative electrode active material particles 205 may be particles composed of the vanadium oxide of the first embodiment.

[0090] The negative electrode active material particles 205 may have a median particle size of 0.1 μm or more and 100 μm or less. When the negative electrode active material particles 205 have a median particle size of 0.1 μm or more, the negative electrode active material particles 205 and the solid electrolyte particles 100 may be well dispersed in the negative electrode 203. Thus, the charge and discharge characteristics of the battery are improved. When the negative electrode active material particles 205 have a median particle size of 100 μm or less, the lithium diffusion rate in the negative electrode active material particles 205 is increased. Thus, the battery 1000 can operate at a high output power.

[0091] The negative electrode active material particles 205 may have a larger median particle size than the solid electrolyte particles 100. Thus, the negative electrode active material particles 205 and the solid electrolyte particles 100 may be well dispersed.

[0092] To improve the energy density and output of the battery 1000 , in the negative electrode 203 , the ratio of the volume of the negative electrode active material particles 205 to the sum of the volume of the negative electrode active material particles 205 and the volume of the solid electrolyte particles 100 may be 0.30 or more and 0.95 or less.

[0093] In order to improve the energy density and output power of the battery 1000 , the negative electrode 203 may have a thickness of 10 μm or more and 500 μm or less.

[0094] The solid electrolyte particles 100 included in the negative electrode 203 may be a sulfide solid electrolyte, a halide solid electrolyte, an oxide solid electrolyte, or a polymer solid electrolyte.

[0095] In the present disclosure, "sulfide solid electrolyte" refers to a solid electrolyte containing sulfur. "Oxide solid electrolyte" refers to a solid electrolyte containing oxygen. The oxide solid electrolyte may contain anions other than oxygen (excluding sulfur anions and halogen anions). "Halide solid electrolyte" refers to a solid electrolyte containing halogen elements and no sulfur. The halide solid electrolyte may contain not only halogen elements but also oxygen.

[0096] Examples of sulfide solid electrolytes are: Li 2 SP 2 S 5 , Li 2 S-SiS 2 , Li 2 SB 2 S 3 , Li 2 S-GeS 2 , Li 3.25 Ge 0.25 P 0.75 S 4 or Li10 G 2 S 12 .

[0097] An example of a halide solid electrolyte is Li a Me b Y c X 6 A compound represented by . Here, the mathematical formulas a+mb+3c=6 and c>0 are satisfied. Me is at least one selected from the group consisting of metal elements and semi-metal elements other than Li and Y. X is at least one element selected from the group consisting of F, Cl, Br and I. The value of m represents the valence of Me.

[0098] "Semi-metallic elements" are B, Si, Ge, As, Sb and Te. "Metallic elements" are all elements contained in Groups 1 to 12 of the periodic table (excluding H) and all elements contained in Groups 13 to 16 of the periodic table (excluding B, Si, Ge, As, Sb, Te, C, N, P, O, S and Se).

[0099] In order to improve the ionic conductivity of the halide solid electrolyte, Me can be at least one element selected from the group consisting of Mg, Ca, Sr, Ba, Zn, Sc, Al, Ga, Bi, Zr, Hf, Ti, Sn, Ta and Nb.

[0100] Another example of a halide solid electrolyte is Li α’ Me' β O γ X δ A compound represented by . Here, α', β, γ and δ are all values ​​greater than 0, Me' is at least one element selected from the group consisting of metal elements and semi-metal elements other than Li, X is at least one element selected from the group consisting of Cl, Br and I, and satisfies the mathematical formula: 0.9≤α'≤1.2, β=1.0, 1.0≤γ≤1.3 and 3.6≤δ≤4.0.

[0101] Examples of oxide solid electrolytes are:

[0102] (i)LiTi 2 (PO 4 ) 3 or a NASICON-type solid electrolyte such as an element substitution body thereof;

[0103] (ii) (LaLi)TiO 3 Such a perovskite-type solid electrolyte;

[0104] (iii)Li 14 ZnGe 4 O16 , Li 4 SiO 4 、LiGeO 4 or a LISICON type solid electrolyte such as an element substitution body thereof;

[0105] (iv)Li 7 La 3 Zr 2 O 12 Or a garnet-type solid electrolyte such as an element substitution body thereof;

[0106] or

[0107] (v)Li 3 PO 4 or its N-substituted form.

[0108] Examples of polymer solid electrolytes include compounds of polymer compounds and lithium salts. The polymer compound may have an ethylene oxide structure. The polymer compound having an ethylene oxide structure has a higher ion conductivity because it can contain a large amount of lithium salt. The polymer solid electrolyte may be, for example, a composite compound of polyethylene oxide and a lithium salt. Examples of such polymer solid electrolytes include lithium bis(trifluoromethanesulfonyl)imide.

[0109] Examples of lithium salts are: LiPF 6 , LiBF 4 、LiSbF 6 、LiAsF 6 、LiSO 3 CF 3 、LiN(SO 2 CF 3 ) 2 、LiN(SO 2 C 2 F 5 ) 2 、LiN(SO 2 CF 3 )(SO 2 C 4 F 9 ) or LiC(SO 2 CF 3 ) 3 One lithium salt selected from these may be used alone, or a mixture of two or more lithium salts selected from these may be used.

[0110] The positive electrode 201 contains a material that can store and release metal ions such as lithium ions. The positive electrode 201 contains, for example, a positive electrode active material (for example, positive electrode active material particles 204).

[0111] Examples of positive electrode active materials include: lithium-containing transition metal oxides, transition metal fluorides, polyanionic materials, fluorinated polyanionic materials, transition metal sulfides, transition metal oxysulfides or transition metal oxynitrides. Examples of lithium-containing transition metal oxides include: Li(Ni, Co, Al)O 2 、Li(Ni,Co,Mn)O 2 , or LiCoO 2 .

[0112] In the present disclosure, “(A, B, C)” means “at least one selected from the group consisting of A, B, and C”.

[0113] From the perspective of cost and safety of the battery 1000 , lithium phosphate may be used as the positive electrode active material.

[0114] The positive electrode active material particles 204 may have a median particle size of 0.1 μm or more and 100 μm or less. When the positive electrode active material particles 204 have a median particle size of 0.1 μm or more, the positive electrode active material particles 204 and the solid electrolyte particles 100 can be well dispersed in the positive electrode 201. Thus, the charge and discharge characteristics of the battery are improved. When the positive electrode active material particles 204 have a median particle size of 100 μm or less, the lithium diffusion rate in the positive electrode active material particles 204 is increased. Thus, the battery 1000 can operate at a high output power.

[0115] The positive electrode active material particles 204 may have a larger median particle size than the solid electrolyte particles 100. Thus, the positive electrode active material particles 204 and the solid electrolyte particles 100 may be well dispersed.

[0116] In order to improve the energy density and output of the battery 1000 , in the positive electrode 201 , the ratio of the volume of the positive electrode active material particles 204 to the sum of the volume of the positive electrode active material particles 204 and the volume of the solid electrolyte particles 100 may be 0.30 or more and 0.95 or less.

[0117] The electrode material 1100 is included in the positive electrode 201, for example. In order to prevent the electrode active material particles 206 from reacting with the solid electrolyte particles 100, a coating layer 216 may be formed on the surface of the electrode active material particles 206. Thus, the increase in the reaction overvoltage of the battery can be suppressed. Examples of the coating material included in the coating layer 216 include: a sulfide solid electrolyte, an oxide solid electrolyte, a polymer solid electrolyte, or a halide solid electrolyte.

[0118] The coating material may be a halide solid electrolyte material or an oxide solid electrolyte material. The halide solid electrolyte material may contain F. Thus, the stability of the coating material at high potential is improved. Therefore, the battery 1000 has a high charge and discharge efficiency. The oxide solid electrolyte may be lithium niobate or a polyanion material having excellent stability even at high potential. Thus, the battery 1000 has a high charge and discharge efficiency.

[0119] In order to improve the energy density and output power of the battery 1000 , the positive electrode 201 may have a thickness of 10 μm or more and 500 μm or less.

[0120] The solid electrolyte particles 100 included in the positive electrode 201 may be a sulfide solid electrolyte, a halide solid electrolyte, an oxide solid electrolyte, a polymer solid electrolyte, or an organic polymer solid electrolyte.

[0121] The electrolyte layer 202 contains an electrolyte material. The electrolyte material is, for example, a solid electrolyte material. The electrolyte layer 202 may be a solid electrolyte layer. The solid electrolyte material contained in the electrolyte layer 202 may be a sulfide solid electrolyte, a halide solid electrolyte, or a polymer solid electrolyte.

[0122] The electrolyte layer 202 may have a thickness of 1 μm or more and 100 μm or less. When the electrolyte layer 202 has a thickness of 1 μm or more, the positive electrode 201 and the negative electrode 203 are less likely to short-circuit. When the electrolyte layer 202 has a thickness of 100 μm or less, the battery 1000 can operate at a high output power.

[0123] In order to facilitate the transfer of lithium ions and improve the output characteristics of the battery, at least one selected from the group consisting of the positive electrode 201, the electrolyte layer 202, and the negative electrode 203 may contain a non-aqueous electrolyte, a gel electrolyte, or an ionic liquid.

[0124] The non-aqueous electrolyte contains a non-aqueous solvent and a lithium salt dissolved in the non-aqueous solvent. Examples of the non-aqueous solvent include: a cyclic carbonate solvent, a chain carbonate solvent, a cyclic ether solvent, a chain ether solvent, a cyclic ester solvent, a chain ester solvent or a fluorine solvent. Examples of cyclic carbonate solvents include: ethylene carbonate, propylene carbonate or butylene carbonate. Examples of chain carbonate solvents include: dimethyl carbonate, ethyl methyl carbonate or diethyl carbonate. Examples of cyclic ether solvents include: tetrahydrofuran, 1,4-dioxane or 1,3-dioxolane. Examples of chain ether solvents include: 1,2-dimethoxyethane or 1,2-diethoxyethane. Examples of cyclic ester solvents include: γ-butyrolactone. Examples of chain ester solvents include: methyl acetate. Examples of fluorine solvents include: fluoroethylene carbonate, methyl fluoropropionate, fluorobenzene, fluoroethyl methyl carbonate or fluorodimethylene carbonate. One nonaqueous solvent selected from these may be used alone, or a mixture of two or more nonaqueous solvents selected from these may be used.

[0125] Examples of lithium salts are: LiPF 6 , LiBF 4 、LiSbF 6 、LiAsF 6 、LiSO 3 CF 3 、LiN(SO 2 CF 3 ) 2 、LiN(SO 2 C 2 F 5 ) 2 、LiN(SO 2 CF 3 )(SO 2 C 4 F 9 ) or LiC(SO 2 CF 3 ) 3 One lithium salt selected from these may be used alone. Alternatively, a mixture of two or more lithium salts selected from these may be used. The concentration of the lithium salt is, for example, in the range of 0.5 mol / liter or more and 2 mol / liter or less.

[0126] As the gel electrolyte, a polymer material impregnated with a non-aqueous electrolyte can be used. Examples of the polymer material include polyethylene oxide, polyacrylonitrile, polyvinylidene fluoride, polymethyl methacrylate, or a polymer having an ethylene oxide bond.

[0127] Examples of cations contained in ionic liquids are:

[0128] (i) aliphatic chain quaternary salts such as tetraalkylammonium or tetraalkylphosphonium;

[0129] (ii) an aliphatic cyclic ammonium such as a pyrrolidinium, morpholinium, imidazolinium, tetrahydropyrimidinium, piperazinium or piperidinium; or

[0130] (iii) Nitrogen-containing heterocyclic aromatic cations such as pyridinium and imidazolium cations.

[0131] Examples of anions contained in ionic liquids are: PF 6 - , BF 4 - , SbF 6 - , AsF 6 - 、SO 3 CF 3 - 、N(SO 2 CF 3 ) 2 - 、N(SO 2 C 2 F 5 ) 2 - 、N(SO 2 CF 3 )(SO 2 C 4 F 9 ) - or C(SO 2 CF 3 ) 3 - .

[0132] The ionic liquid may contain a lithium salt.

[0133] At least one selected from the group consisting of the positive electrode 201 , the electrolyte layer 202 , and the negative electrode 203 may contain a binder for the purpose of improving adhesion between particles.

[0134] Examples of binders include polyvinylidene fluoride, polytetrafluoroethylene, polyethylene, polypropylene, aramid resin, polyamide, polyimide, polyamide-imide, polyacrylonitrile, polyacrylic acid, polymethyl acrylate, polyethyl acrylate, polyhexyl acrylate, polymethacrylic acid, polymethyl methacrylate, polyethyl methacrylate, polyhexyl methacrylate, polyvinyl acetate, polyvinyl pyrrolidone, polyether, polyether sulfone, hexafluoropolypropylene, styrene butadiene rubber or carboxymethyl cellulose. As a binder, a copolymer can be used. Examples of the binder include copolymers of two or more materials selected from the group consisting of tetrafluoroethylene, hexafluoroethylene, hexafluoropropylene, perfluoroalkyl vinyl ether, vinylidene fluoride, chlorotrifluoroethylene, ethylene, propylene, pentafluoropropylene, fluoromethyl vinyl ether, acrylic acid and hexadiene. A mixture of two or more selected from the above materials can be used.

[0135] For the purpose of improving electron conductivity, at least one selected from the positive electrode 201 and the negative electrode 203 may contain a conductive auxiliary agent.

[0136] Examples of conductive additives are:

[0137] (i) Graphites such as natural graphite or artificial graphite;

[0138] (ii) carbon blacks such as acetylene black or Ketjen black;

[0139] (iii) conductive fibers such as carbon fibers or metal fibers;

[0140] (iv) fluorinated carbons;

[0141] (v) Metal powders such as aluminum;

[0142] (vi) Conductive whiskers such as zinc oxide or potassium titanate;

[0143] (vii) a conductive metal oxide such as titanium oxide; or

[0144] (viii) Conductive polymer compounds such as polyaniline, polypyrrole or polythiophene.

[0145] For cost reduction, the conductive auxiliary agent (i) or (ii) described above may be used.

[0146] The negative electrode 203 may include not only the negative electrode active material particles 205 but also a conductive auxiliary agent 207. Examples of the material of the conductive auxiliary agent 207 are as described above.

[0147] The conductive agent 207 may cover at least a portion of the surface of the negative electrode active material particles 205. This increases the contact area between the conductive agent 207 and the negative electrode active material particles 205. As a result, the battery resistance is reduced and the output can be increased.

[0148] In the negative electrode 203 , the ratio of the volume of the conductive auxiliary agent 207 to the sum of the volume of the negative electrode active material particles 205 and the volume of the conductive auxiliary agent 207 may be 0.01 or more and 0.4 or less.

[0149] Figure 2 A cross-sectional view of an electrode material 1100 according to the second embodiment is shown. Figure 2 The electrode material 1100 shown may be contained in the negative electrode 203. In order to prevent the solid electrolyte particles 100 from reacting with the negative electrode active material (i.e., the electrode active material particles 206), a coating layer 216 may be formed on the surface of the electrode active material particles 206. As a result, the battery has a high charge and discharge efficiency. Therefore, the vanadium oxide of the first embodiment contained in the negative electrode 203 may be coated with a coating material.

[0150] Examples of the coating material contained in the coating layer 216 include a sulfide solid electrolyte, an oxide solid electrolyte, a polymer solid electrolyte, or a halide solid electrolyte.

[0151] Examples of sulfide solid electrolytes are: Li 2 SP 2 S 5 Examples of oxide solid electrolytes include trilithium phosphate. Examples of polymer solid electrolytes include composite compounds of polyethylene oxide and lithium salts. Examples of such polymer solid electrolytes include lithium bis(trifluoromethanesulfonyl)imide.

[0152] Examples of the shape of the battery of the second embodiment include a coin shape, a cylindrical shape, a square shape, a sheet shape, a button shape, a flat shape, or a laminated shape.

[0153] The battery of the second embodiment can be manufactured, for example, by preparing a material for forming a positive electrode, a material for forming an electrolyte layer, and a material for forming a negative electrode, and fabricating a stack having a positive electrode, an electrolyte layer, and a negative electrode arranged in this order by a known method.

[0154] Example

[0155] The present disclosure is described in more detail below using examples and comparative examples. The vanadium oxide of the example may have a composition formula (1): Li 3+x+α V 1-x M x O 4+α / 2 express.

[0156] (Example 1)

[0157] [Production of vanadium oxide]

[0158] Li as raw material powder 2 CO 3(manufactured by Kojun Chemical Research Institute Co., Ltd., purity 99.9%), V 2 O 5 (manufactured by Kojun Chemical Research Institute Co., Ltd., purity 99.9%) and TiO 2 (manufactured by Kojun Chemical Research Institute Co., Ltd., purity 99.9%) to form Li 2 CO 3 :V 2 O 5 :TiO 2 =1.525:0.475:0.05 in molar ratio. 2 CO 3 The amount of 1 mass % excess was prepared relative to the above composition. That is, relative to the Li 2 CO 3 The mass of Li was prepared in an excess amount of 1 mass % 2 CO 3 . These raw material powders are mixed in a mortar to obtain a mixed powder. The obtained mixed powder is pre-fired at 600°C for 3 hours in the air. The obtained pre-fired powder is formally fired at 920°C for 15 hours in the air. The heating rate of the pre-fired and formal firing is 10°C per minute, and the cooling rate is 5°C per minute. In this way, the vanadium oxide of Example 1 is obtained.

[0159] In the vanadium oxide of Example 1, x in the composition formula (1) is 0.05 and α is 0.06.

[0160] x was determined by analyzing the amount of Ti using an ICP emission spectrophotometer (PS3520VDDII manufactured by Hitachi High-Tech Corporation). α was determined by analyzing the amount of Li using an atomic absorption spectrophotometer (Z-2300 manufactured by Hitachi High-Technologies Corporation) and the result of the analysis and the result of the amount of Ti (i.e., the value of x).

[0161] [Battery production]

[0162] In an argon atmosphere having a dew point of -60°C or less, the vanadium oxide of Example 1 and the solid electrolyte Li were prepared at a volume ratio of 60:40. 3 PS 4 These materials were mixed in an agate mortar to obtain a negative electrode mixture.

[0163] The solid electrolyte Li is stacked in an insulating tube with an inner diameter of 9.5 mm. 3 PS 4(80 mg) and a negative electrode mixture (6.5 mg) were mixed to obtain a laminate. A pressure of 360 MPa was applied to the laminate to form a solid electrolyte layer and a negative electrode. The solid electrolyte layer had a thickness of 500 μm.

[0164] Next, Li (thickness: 300 μm) was stacked on the solid electrolyte layer, and a pressure of 80 MPa was applied to the stack to form a positive electrode.

[0165] Next, current collectors made of stainless steel were attached to the positive electrode and the negative electrode, and current collecting leads were attached to the current collectors.

[0166] Finally, an insulating ferrule is used to block the inside of the insulating cylinder from the outside atmosphere, thereby hermetically sealing the inside of the cylinder.

[0167] Through the above operation, the battery of Example 1 is obtained. It should be noted that the battery of Example 1 is a monopolar test battery with a negative electrode as a working electrode and a positive electrode as a counter electrode, which is used to test the performance of the negative electrode. In detail, the working electrode uses the negative electrode of the test object, and the counter electrode uses a sufficient amount of appropriate active material sufficient to satisfy the reaction of the working electrode. Since this test battery is used to test the performance of the negative electrode, metal Li is used as the counter electrode. The negative electrode whose performance has been tested using such a test battery can be used as a secondary battery, for example, by combining it with a positive electrode containing a positive electrode active material as described in the above embodiment, such as a Li-containing transition metal oxide.

[0168] [Charge and discharge test]

[0169] Figure 3 This is a graph showing the initial discharge characteristics of the battery of Example 1. The horizontal axis represents the discharge capacity and the vertical axis represents the voltage. Figure 3 The results shown were determined by the following method.

[0170] The battery of Example 1 was used to perform a charge and discharge test as follows. It should be noted that, as described above, the battery produced in Example 1 is a single-pole test battery, which is equivalent to a half-cell of the negative electrode. Therefore, in Example 1, the direction in which the potential of the half-cell decreases when the Li ions are inserted into the negative electrode is called charging, and the direction in which the potential increases is called discharging. That is, the charging in Example 1 is essentially (i.e., in the case of a full battery) discharging, and the discharging in Example 1 is essentially charging.

[0171] The battery of Example 1 was placed in a constant temperature chamber maintained at 25°C.

[0172] The battery of Example 1 was charged to a voltage of 0.3 V at a current value that formed a 0.1C rate (10 hour rate) relative to the theoretical capacity of the battery. Next, the battery of Example 1 was discharged to a voltage of 2.5 V at a current value that formed a 0.05C rate.

[0173] As a result of the charge and discharge test, the battery of Example 1 had an initial discharge capacity of 354 mAh / g.

[0174] (Examples 2 to 7 and Comparative Example 1)

[0175] [Production of vanadium oxide]

[0176] In Example 2, Li 2 CO 3 An excess amount of 5 mass % was prepared. Except for this, the vanadium oxide of Example 2 was prepared in the same manner as in Example 1. The values ​​of x and α in the composition formula (1) were determined in the same manner as in Example 1. In Example 2, x was 0.05 and α was 0.14.

[0177] In Example 3, Li 2 CO 3 An excess amount of 10 mass % was prepared. Except for this, the vanadium oxide of Example 3 was prepared in the same manner as in Example 1. The values ​​of x and α in the composition formula (1) were determined in the same manner as in Example 1. In Example 3, x was 0.05 and α was 0.24.

[0178] In Example 4, Li 2 CO 3 An excess amount of 15 mass % was prepared. Except for this, the vanadium oxide of Example 4 was prepared in the same manner as in Example 1. The values ​​of x and α in the composition formula (1) were determined in the same manner as in Example 1. In Example 4, x was 0.05 and α was 0.57.

[0179] In Example 5, Li 2 CO 3 An excess amount of 30% by mass was prepared. Except for this, the vanadium oxide of Example 5 was prepared in the same manner as in Example 1. The values ​​of x and α in the composition formula (1) were determined in the same manner as in Example 1. In Example 5, x was 0.05 and α was 0.93.

[0180] In Example 6, Li 2 CO 3 :V 2 O 5 =1.5:0.5 molar ratio to prepare Li 2 CO 3 and V 2 O 5 Among them, Li 2 CO 3An excess amount of 10 mass % was prepared. Except for the above, the vanadium oxide of Example 6 was prepared in the same manner as in Example 1. The values ​​of x and α in the composition formula (1) were determined in the same manner as in Example 1. In Example 6, x was 0 and α was 0.25.

[0181] In Example 7, Li 2 CO 3 :V 2 O 5 :TiO 2 =1.55:0.45:0.1 molar ratio to prepare Li 2 CO 3 、V 2 O 5 and TiO 2 Among them, Li 2 CO 3 An excess amount of 10 mass % was prepared. Except for the above, the vanadium oxide of Example 7 was prepared in the same manner as in Example 1. The values ​​of x and α in the composition formula (1) were determined in the same manner as in Example 1. In Example 7, x was 0.1 and α was 0.32.

[0182] Comparative Example 1: No excess Li was added 2 CO 3 Except for the above, the vanadium oxide of Comparative Example 1 was prepared in the same manner as in Example 1. The values ​​of x and α in the composition formula (1) were determined in the same manner as in Example 1. In Comparative Example 1, x was 0.05 and α was 0.03.

[0183] [Charge and discharge test]

[0184] Batteries using the vanadium oxides of Examples 2 to 8 and Comparative Example 1 as negative electrodes were prepared in the same manner as in Example 1, and the initial discharge capacity was measured in the same manner as in Example 1. The measurement results are shown in Table 1.

[0185] [Table 1]

[0186]

[0187] (Inspection)

[0188] As can be seen from Table 1, the battery using the vanadium oxide represented by the composition formula (1) as the active material has a high discharge capacity.

[0189] Comparison of Comparative Example 1 with Examples 1 to 5 shows that, when α is larger than 0.03, a high discharge capacity can be achieved.

[0190] Comparison of Comparative Example 1 with Examples 1 to 7 shows that even when x is other than 0.05, a high discharge capacity can be achieved when α is greater than 0.03. That is, even when x is 0, a high discharge capacity can be achieved when α is greater than 0.03.

[0191] It should be noted that the same effect can be expected when at least one selected from the group consisting of other tetravalent metal elements is used as M instead of Ti. This is because elements having the same valence of 4 as Ti have properties similar to those of Ti.

[0192] As described above, the vanadium oxide of the present disclosure is suitable for providing a battery having excellent charge and discharge characteristics.

[0193] Industrial Applicability

[0194] The vanadium oxide disclosed in the present invention can be used as a battery material, for example, as a material for an all-solid-state lithium-ion secondary battery.

Claims

1. A vanadium oxide, It is composed of the formula (1): Li 3+x+α V 1-x M x O 4+α / 2 express, Here, in the composition formula (1), 0.03<α<1.0 and 0≤x<1.0 are satisfied, and M is at least one selected from the group consisting of tetravalent metal elements.

2. The vanadium oxide according to claim 1, In the composition formula (1), 0 <x<1.0。 3. The vanadium oxide according to claim 2, In the composition formula (1), 0 <x≤0.1。 4. The vanadium oxide according to claim 1, In the composition formula (1), M contains Ti.

5. The vanadium oxide according to claim 1, In the composition formula (1), 0.04≤α≤0.95 is satisfied.

6. The vanadium oxide according to claim 5, In the composition formula (1), 0.06≤α≤0.93 is satisfied.

7. The vanadium oxide according to claim 6, In the composition formula (1), 0.1≤α≤0.6 is satisfied.

8. The vanadium oxide according to claim 7, In the composition formula (1), 0.14≤α≤0.57 is satisfied.

9. A battery, It has: positive electrode, Negative electrode, and an electrolyte layer disposed between the positive electrode and the negative electrode, The negative electrode comprises the vanadium oxide according to any one of claims 1 to 8.

10. The battery according to claim 9, wherein The negative electrode further includes a conductive aid.

Citation Information

Patent Citations

  • Negative electrode material for nonaqueous secondary battery and nonaqueous secondary battery using the same

    JP2008077847A

  • Co-firing type all-solid state battery

    WO2019044902A1